Penggunaan kapang Rhizopus oligosporus dalam pembuatan biofoam cup berbahan dasar sabut kelapa dan tepung kedelai - Dewi Yunita; Rafiqah Rafiqah; Ismail Sulaiman; Eti Indarti (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Biofoam is an alternative packaging to replace styrofoam because it is renewable and biodegradable. In this study, the coconut fibre were used in the production of biofoam cup with addition of commercial tempe yeast (Rhizopus oligosporus). The purpose of this study was to produce biofoam cup which has the characteristics of water resistant, not easily crushed, and easily decomposed. This study was conducted with a factorial Block Randomized Design (BRD) consisting of 2 factors (the amount of soybean flour (T) amd the length of fermentation (S)). The first factor consisted of three levels (20 g, 24 g, and 28 g). The second factor consisted of three levels (3 days, 4 days, and 5 days). All treatments were carried out with 3 replications so there were 27 experimental units. The biofoam cup was analysed for physical (water absorption and porosity), mechanical (puncture strength and compressive strength), and biodegrability. The results showed that the best biofoam cup were obtained from a combination of using 28 g soybean flour and 3 days fermentation. The biofoam cup has the following characteristics: 73 % of water absorption capacity, 72.3 % of porosity value, 3.27 kg/cm2 of puncture strength value, 3.17 kPa of compressive strength value. The average value of biodegradability value of biofoam cup made from coconut fibre was 48 % suggesting that the analysis should be done more than 14 days